2020
DOI: 10.1002/ejhf.2030
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, trends and institutional variation in 30‐day all‐cause mortality and unplanned readmissions following hospitalisation for heart failure in Australia and New Zealand

Abstract: Aims National 30‐day mortality and readmission rates after heart failure (HF) hospitalisations are a focus of US policy intervention and yet have rarely been assessed in other comparable countries. We examined the frequency, trends and institutional variation in 30‐day mortality and unplanned readmission rates after HF hospitalisations in Australia and New Zealand. Methods and results We included patients >18 years hospitalised with HF at all public and most private hospitals from 2010–15. The primary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 29 publications
2
33
1
Order By: Relevance
“…However, data regarding trends in 30‐day mortality and unplanned readmission rates following HF hospitalization during this period outside of the US are sparse, but needed to get a better barometer of secular trends in countries where health systems are not penalized by higher readmissions rates. In this issue of the Journal, Labrosciano et al 8 . provide new findings that enrich our understanding of this area.…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…However, data regarding trends in 30‐day mortality and unplanned readmission rates following HF hospitalization during this period outside of the US are sparse, but needed to get a better barometer of secular trends in countries where health systems are not penalized by higher readmissions rates. In this issue of the Journal, Labrosciano et al 8 . provide new findings that enrich our understanding of this area.…”
Section: Figurementioning
confidence: 93%
“…Notably, Labrosciano et al 8 . report a substantial decline in unadjusted 30‐day mortality risk (12.5% to 8.1%) but a lesser decline in 30‐day unplanned readmission rate (23.2% to 21.9%) for HF patients.…”
Section: Figurementioning
confidence: 99%
“…The second study providing important insights into HF epidemiology comes from Australia and New Zealand and considered ∼150 000 patients hospitalized for HF in all the public and private hospitals of these countries between 2010 and 2015 4 . Thirty‐day mortality was 10.7% and 30‐day hospitalization rate was 22.3%, with risk standardized rates declining over time, and risk estimates varying among hospitals.…”
Section: Epidemiologymentioning
confidence: 99%
“…Changes in the epidemiology and characteristics of cardiogenic shock and acute HF have occurred in the last years. [10][11][12][13] Consistently, a systematic review and meta-regression of 285 studies, representing 15 million acute HF events, found a decline in 30-day mortality [odds ratio (OR) for a 10-year increment, 0.74, 95% confidence interval (CI) 0.61-0.91, P = 0.004] and 1-year mortality (OR 0.86, 95% CI 0.77-0.96, P = 0.007) after acute HF, in the last four decades. However, 30-day and 1-year readmission rates were unchanged.…”
Section: Epidemiologymentioning
confidence: 99%